STUDI PERENCANAAN STRUKTUR PONDASI TIANG PANCANG GEDUNG FAKULTAS SYARIAH IAIN PONOROGO - Lin Sintyawati; Sigit Winarto; Ahmad Ridwan; Agata Iwan Candra (Jurnal Manajemen Teknologi & Teknik Sipil, 2018)
The foundation is an important part of a building. In this calculation, I use the Meyerhoff method, and it is based on the results of the analysis of the carrying capacity of a single or group foundation. The results of the loading analysis that occurred in the Islamic Faculty Building IAIN Ponorogo 379,198.5 kg. The results of sondir calculations carried out by hard soil depths reached a depth of 5.8 meters. For the calculation of pile, foundations used a diameter of 40 cm with threaded reinforcement D16 distance 125 with contents of reinforcement 5 and said SAFE. The calculation result of one-way shear force control = 1,085.34 tons> Nominal Shear Force = 348.05 tons is said to be SAFE. The calculation of the Two-Way Shear Force Control = 1,272.45 tons> Nominal Shear Force = 877.91 tons is said to be SAFE. The pile foundation will experience cracks if there is a moment of 58,278,400 tons / m2 <150 tons / m2 maximum allowable moment, and it is said to be SAFE, and the decrease that will occur is 4.644 mm <360 mm, the allowable decrease is said to be SAFE.Pondasi merupakan bagian penting pada suatu bangunan Gedung. Dalam perhitungan ini saya menggunakan metode mayerhoff dan perhitungan berdasarkan hasil analisis daya dukung pondasi tunggal maupun kelompok. Hasil analisis pembebanan yang terjadi pada Gedung Fakultas Syariah IAIN Ponorogo379.198,5 kg. Hasil perhitungan sondir yang dilakukan kedalaman tanah keras mencapai kedalaman 5,8 meter. Perhitungan pondasi tiang pancang mengunakan diameter 40 cm dengan tulangan besi ulir D16 jarak 125 dengan isi 5 tulangan, dan dikatakan AMAN. Hasil Perhitungan Kontrol Gaya Geser Satu Arah = 1.085,34 ton > Gaya Geser Nominal = 348,05 ton dikatakan AMAN. Perhitungan Kontrol Gaya Geser Dua Arah = 1.272,45 ton > Gaya Geser Nominal = 877,91 ton dikatakan AMAN, pondasi tiang pancang tersebut akan mengalami keretakan apabila terjadi momen sebesar 58.278.400 ton/m2 < 150 ton/m2 momen maksimal yang diijinkan dan dikatakan AMAN dan penurunan yang akan terjadi sebesar 4,644 mm < 360 mm penurunan yang diijinkan dan dikatakan AMAN.